Bacterial composition and physicochemical characteristics of sorghum based on environmental factors in different regions of China - Xie, Peiyun; Shao, Mingbo; Deng, Xiaofeng; Ren, Yan; Chen, Manjing; Jiang, Yuwen; Shen, Jiaqi (Frontiers in Microbiology, 2024)
The fermentation process for Jiang-flavoured baijiu using sorghum as the raw material involves a variety of microorganisms. However, the specific physicochemical characteristics of sorghum and microbial composition on its surface have not been fully elucidated. We aimed to perform a comprehensive comparative analysis of the variations in physicochemical properties and surface microflora in waxy sorghum samples from three prominent production regions in China (Renhuai, Jinsha,, and Duyun). In addition, mMultivariate statistical assessments were conducted that incorporated local soil and climate variables. The results showed that Cyanobacteria, unclassified bacteria, Proteobacteria, Firmicutes, and Bacteroidota were the dominant bacteria in these regions. These bacteria were associated with ethyl acetate, ethyl caprylate, ethyl lactate,, and butyl groups, which synergistically produce flavourful substancescompounds. The surface bacterial communities were affected by soil total phosphorus, altitude, diurnal temperature range, monthly mean temperature, precipitation,, and effective accumulated temperature. The findings of this study provide a new perspective on microorganisms related to Jiang-flavoured baijiu and can help establish a reference for the stability of liquor quality.